CRIMINOLOGY ANALYSIS OF ENVIRONMENTAL CRIME IN UKRAINE: FROM THE ORDINARY SITUATION TO THE CONTEXT OF WAR (Bulletin of criminological association of Ukraine, 2023)
The article is devoted to the description of the main indicators of the state of environmental crime in Ukraine. It was established that systematic criminal practices of exploitation of the environment showed their stability even during the war. In 2022, the level of crime against the environment reached 4,018 criminal offenses, of which 742 were misdemeanors and 3,276 were felonies. In addition to the reduction of the territory of statistical accounting due to the temporary occupation of a part of the territory of Ukraine, the active conduct of hostilities, as well as significant migration of the population, the departure of about 8 million citizens outside the country, an equally important shift in law enforcement practice regarding damage to the environment, in particular towards qualifications as war crimes, i.e. under Art. 438 of the Criminal Code of Ukraine. Ukraine faced what previously, including in the period from 2014 to 24.02.2022, was the exception rather than the rule – war crimes against the environment
Keywords: environment; environmental crime; state; dynamics; illegal logging; illegal hunting; war; war crimes against the environment; combating crime